Assessing the Role of Community-Based Screening in Early Detection of Hepatocellular Carcinoma in Hepatitis B and C at a Tertiary Care Hospital - Ayesha Javaid, Anila Riyaz, Bilal Masood, Muhammad Tariq Hamayun Khan, Mumtaz Lakho, Zahida Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatocellular carcinoma (HCC) is a major cause of cancer-related mortality worldwide, especially in countries with a high burden of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections. In Pakistan, late-stage diagnosis remains a significant challenge due to limited surveillance and delayed access to tertiary care. Community-based screening offers a promising approach to detect HCC at earlier, more treatable stages. Objective: To evaluate the effectiveness of community-based hepatitis screening in the early detection of HCC among HBV- and HCV-infected patients referred to a tertiary care hospital. Methods: This cross-sectional observational study was conducted at Bolan Medical University Hospital, Quetta, from June 2022 to June 2023. A total of 70 patients aged 30–70 years with HBV or HCV infection were referred from rural community screening camps. All underwent abdominal ultrasound, serum alpha-fetoprotein (AFP) testing, and contrast-enhanced MRI/CT where indicated. Diagnosed HCC cases were staged using the Barcelona Clinic Liver Cancer (BCLC) system. Results: Of the 70 patients, 14 (20%) were diagnosed with HCC. Among these, 9 patients (64.3%) were classified as BCLC Stage A, 3 (21.4%) as Stage B, and 2 (14.3%) as Stage C. No patients presented at Stage D. Early-stage detection was notably higher than in typical hospital-based presentations. Conclusion: Community-based screening significantly improves early-stage detection of HCC in high-risk populations. Integrating ultrasound and AFP testing into outreach programs may shift diagnosis to curative stages and reduce liver cancer mortality in resource-limited settings. Keywords: Hepatocellular carcinoma, community screening, hepatitis B, hepatitis C, BCLC staging, early detection, Pakistan, tertiary hospital